Strategic alliance between information intensive services and supply chain integration: impact on firm performance - Roy, Supriyo; Satpathy, Biswajit (Brazilian Journal of Operations & Production Management, 2019)
Goal: This Survey-based empirical research is aimed to theorize and assess a structural model that incorporates strategic alliance between Information Intensive Services (IIS) and Supply Chain Integration (SCI) and its impact on Firm Performance (FP), with special reference to Indian business houses. Design / Methodology / Approach: This paper proposes a hypothesis model within the decision-making framework that offers strategic alliance tool for managers in the area of supply chain to operationalize business decisions. Samples of more than 210 primary data sets are collected from population of different industries in India by a proper sampling method and by framing questionnaires. The relationship, as proposed in the hypothesis model, is assessed empirically by using statistical techniques called Structural Equation Modeling. Results: Practitioners may expect improved supply chain performance through strategic alliance between information intensive services and supply chain integration, as it is demanded industries in this Industry 4.0 era. Limitations: The hypothesis framed by western standards seems to be obvious; however, considering the Indian business scenario, where the supply chain and technology of information systems are almost a new concept in most firms, this seems to be a valid area of research. Practical Implications: Research conceptualizes and develops different dimensions of information-intensive services that offer empirical support for the adoption of proper information system to improve performance within an integrated supply chain. Originality / Value: This survey-based empirical research will ‘coordinate and highlight the issue of integration’ of Enterprise Information Systems within the organizational supply chain.